A Numerical Investigation of the P-Delta Effect on Steel Frames with Semi-rigid Connections and Soft Stories - Khelassi, Amar; Messaoudi, Abdelghaffar; Djireb, Samir; Mabrouki, Abdelhak (Engineering, Technology & Applied Science Research, 2025)
The physical and mechanical properties of a structure after a large displacement are significantly different from those of its initial state without deformation. The P-Delta analysis is particularly important for multi-story structures subjected to lateral loads. This study focuses on the numerical analysis of a steel frame using the finite element method. The proposed frame structures have been modeled in SAP2000 to evaluate the internal forces and lateral displacement of steel frames, subjected to concentrated lateral loads at the story levels. The P-Delta effects were evaluated and compared employing linear static analysis of a steel frame with and without soft story and semi-rigid connections. The results of the numerical method were compared with those reported in the literature. The novelty of the present study lies in the combination of semi-rigid connections, soft story, and P-Delta effect. This combination has a significant impact on the behavior of steel frames, especially on inter-story drifts.